Analysis of the Effectiveness of Electronic Case Handling in Enhancing Legal Certainty and Accountability of Judicial Institutions in Indonesia - Althea Serafim Kriswabdaru; Berliant Pratiwi (Universitas Sains dan Teknologi Komputer, 2026)
This study examines the effectiveness of the implementation of electronic courts (e-Courts) in enhancing legal certainty and institutional accountability in Indonesia. Using a mixed methods sequential explanatory design, the research combines quantitative data from 100 respondents, including judges, lawyers, and court staff, with qualitative insights from in-depth interviews with 10 key informants. Quantitative analysis was conducted using Structural Equation Modeling (PLS-SEM) to assess the relationships among e-Court implementation, organizational readiness, legal certainty, and accountability, while thematic analysis was used to interpret qualitative findings. The results show that e-Court significantly improves legal certainty and strengthens institutional accountability. Organizational readiness is identified as a key mediating factor influencing system effectiveness. However, challenges such as technical constraints and varying levels of user adaptation remain evident. This study contributes to the literature by providing empirical evidence on the impact of digitalization in judicial systems and highlights the importance of integrating technological and organizational factors. The findings offer practical implications for policymakers and judicial institutions in optimizing e-Court implementation in Indonesia